2013
DOI: 10.1111/j.1532-950x.2013.12081.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of V‐Loc™ versus Biosyn™ in a one‐layer end‐to‐end anastomosis of equine jejunum

Abstract: V-Loc™ allowed faster construction time and did not cause a decreased anastomosis luminal diameter when compared with Biosyn™. V-Loc™ had a decreased bursting strength compared with Biosyn™, albeit well above pathologic pressures encountered clinically. Use of V-Loc™ may be beneficial for decreasing the amount of exposed suture material because of the absence of knots after construction and has the potential to result in decreased adhesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 13 publications
7
60
1
2
Order By: Relevance
“…Both intracorporeal and extracorporeal knot-tying require significant training, but even with that it has been observed that knots performed laparoscopically are often less safe than those hand-sewn [7]. In cases where knot-tying is difficult or under certain circumstances that so require it, the use of barbed sutures may reduce operative time [8][9][10], surgeon fatigue, and, potentially, the costs [11].…”
Section: Characteristics Of Barbed Suturesmentioning
confidence: 99%
“…Both intracorporeal and extracorporeal knot-tying require significant training, but even with that it has been observed that knots performed laparoscopically are often less safe than those hand-sewn [7]. In cases where knot-tying is difficult or under certain circumstances that so require it, the use of barbed sutures may reduce operative time [8][9][10], surgeon fatigue, and, potentially, the costs [11].…”
Section: Characteristics Of Barbed Suturesmentioning
confidence: 99%
“…Some construction time may be saved by the use of a double‐layer closure with line reversal, but this has been shown to be no different from a standard double‐layer closure and is not routinely used in the authors’ hospital. Single‐layer closure with barbed sutures was chosen because this is a common application of the material …”
Section: Discussionmentioning
confidence: 99%
“…The proposed benefits of using barbed sutures include even tension distribution, decreased construction time, and decreased amount of suture in the tissue . A reduction in the quantity of suture material and exposed suture possibly leads to less tissue inflammation and decreased knot‐related complications . Studies in human medicine have concluded that the barbed sutures have performed equivalently to conventional absorbable sutures and have not resulted in increased complication rates …”
Section: Introductionmentioning
confidence: 99%
“…The self‐locking, knotless suture is one of the most recent developments in suture technology. This device was first used in plastic surgery, but it has spread widely among other surgical fields . Its application in veterinary medicine has resulted in only a few reports, but its use has already been associated with reduced operative times .…”
Section: Discussionmentioning
confidence: 99%